Business Phenomena in Indonesia - Priyanto, A; Aria, M (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to find out the business phenomena conducted by vloggers in Indonesia through communication media. The method used is qualitative descriptive methods because it aims to gather detailed information, describe existing phenomena, identify problems, make comparisons, and evaluate. The results of this study provide information on how communication media can become a medium that influences promising businesses for vloggers in Indonesia. Therefore, the use of effective and efficient communication media can provide maximum and sustainable results. This research can be useful to find out the influence and benefits of communication media that are increasingly in demand by all groups so that they can influence and provide benefits as well as business fields.